FOUNDATIONS OF RELIGIOUS STYLE IN LINGUISTICS - Bektoshev Otabek (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the conditions, reasons and factors of characterization of religious style in the field of linguistics. In addition, religious style and its main peculiarities, its importance in the social life, and the functional features of religious style are highlighted in the article. As a result of our investigation, the following results were obtained: a) the increase in the need for the creation and significance of religious language, particularly religious texts has been scientifically proved; b) the possibility of religious texts to represent the thoughts of the people, culture and world outlook has been verified; c) the specificity of religious language, religious texts has been revealed; d) the development of religious style as a functional style has been grounded.